A study of the perception of the benefits of customer relationship management (CRM) system in Malaysian private hospitals - Rababah, Khalid; Mohd, Haslina; Ibrahim, Huda (2010)
The implementation of Customer relationship Management (CRM) Systems has been increased within organizations for the purposes of increasing customer loyalty accompany with decreasing expenses and increasing revenues.The perception of the benefits associated with the implementation of CRM systems is an essential step for the adoption and implementation of CRM systems.Therefore, this paper presented the study being conducted to investigate the perception of the CRM systems in the private hospitals in the northern part of Malaysia as there is a lack of adoption of CRM systems in hospitals.Qualitative research approach that is interview based was adapted in the study. The management of 10 private hospitals in the northern part of Malaysia was interviewed.The results revealed no hospital has adopted CRM system.In addition, there is a substantial lack of understanding of the benefits of CRM systems in hospitals.Some hospitals claim that the implementation of CRM system is not of their priorities and there are much important projects as the implementation of Electronic Medical Records (EMD).However, other hospitals indicated for an existence of future plan for the adoption and implementation of CRM system.Another issue that needs to be taken into consideration by the vendors of CRM systems is the high costs associated with the implementation of CRM systems in hospitals.Indeed, both the vendors of CRM systems and the managers of hospitals hold the responsibility of the lack of CRM systems implementation in hospitals.